2019
DOI: 10.3233/thc-199025
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced shRNA delivery by the combination of polyethylenimine, ultrasound, and nanobubbles in liver cancer

Abstract: BACKGROUND: Traditional cancer treatments such as surgery, radiation, and chemotherapy destroy both cancer and normal cells, which limit their clinical application. It is difficult to achieve the best results for any liver cancer patients using any single treatment method. Gene therapy for HCC demands non-invasive, efficient, targeted and safe gene transfection strategies. OBJECTIVE: In this study, a nonviral shRNA gene delivery system utilizing a combination of PEI, US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…37 Accumulating evidence suggests that nanobubbles produce better ultrasound imaging enhancement because of the enhanced permeation and retention (EPR) effect. 38 The EPR effect promotes the accumulation of nanobubbles in tumor tissues, and active biomolecular targeting is able to enhance the specificity of targeting ability in the tumor. 39 For instance, Jiang et al have indicated that herceptin-targeted nanobubble can be used as a good contrast agent for CEUS imaging in Her-2-positive breast cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Accumulating evidence suggests that nanobubbles produce better ultrasound imaging enhancement because of the enhanced permeation and retention (EPR) effect. 38 The EPR effect promotes the accumulation of nanobubbles in tumor tissues, and active biomolecular targeting is able to enhance the specificity of targeting ability in the tumor. 39 For instance, Jiang et al have indicated that herceptin-targeted nanobubble can be used as a good contrast agent for CEUS imaging in Her-2-positive breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike microbubbles, nanobubbles with size below 500 nm are sufficiently small to pass through submucosal layers 37 . Accumulating evidence suggests that nanobubbles produce better ultrasound imaging enhancement because of the enhanced permeation and retention (EPR) effect 38 . The EPR effect promotes the accumulation of nanobubbles in tumor tissues, and active biomolecular targeting is able to enhance the specificity of targeting ability in the tumor 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The challenges for non-viral gene delivery are the lower efficiency of gene delivery compared with viral vectors, although target/tumor-specific gene delivery can be achieved better than viral vectors. The combination of these viral and non-viral gene delivery procedures might be effective, as evidenced in the recent reports showing that polyethyleneimine, ultrasound, and nanobubbles can effectively deliver shRNA in liver cancer [158].…”
Section: Non-viral Gene Delivery Using Physical Methodsmentioning
confidence: 99%
“…43 The delivery methods for shRNA are similar to the ones proposed for siRNA; 43,44 moreover, also ultrasound-mediated gene delivery and nanobubbles have been investigated in vitro and in vivo for treating liver cancer. 45 Recently, shRNA and long non-coding RNAs (long ncRNAs, lncRNA) have been discovered in the regulation of many cancer pathways. LncRNA originate from different non-coding regions of genes (introns or exons around 200 bp long) and are involved in chromatin remodelling, transcription or post-transcriptional regulation, acting in the cellular differentiation, vitality and disease.…”
Section: Applications Of Exogenous Nucleic Acids In Therapymentioning
confidence: 99%